Simplifying
28x^2 + 8x = 0
Reorder the terms:
8x + 28x^2 = 0
Solving
8x + 28x^2 = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), '4x'.
4x(2 + 7x) = 0
Ignore the factor 4.
Subproblem 1
Set the factor 'x' equal to zero and attempt to solve:
Simplifying
x = 0
Solving
x = 0
Move all terms containing x to the left, all other terms to the right.
Simplifying
x = 0
Subproblem 2
Set the factor '(2 + 7x)' equal to zero and attempt to solve:
Simplifying
2 + 7x = 0
Solving
2 + 7x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + 7x = 0 + -2
Combine like terms: 2 + -2 = 0
0 + 7x = 0 + -2
7x = 0 + -2
Combine like terms: 0 + -2 = -2
7x = -2
Divide each side by '7'.
x = -0.2857142857
Simplifying
x = -0.2857142857
Solution
x = {0, -0.2857142857}